PROFIL RENCANA KEBUTUHAN OBAT DI DINAS KESEHATAN PADA DAERAH TERTINGGAL, PERBATASAN DAN KEPULAUAN (STUDI DI KABUPATEN BELU NUSA TENGGARA TIMUR) - Eva Taulabi; Wahyu Utami; Abdul Rahem (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Drug Requirement Plan (DRP) is the basic consideration of providing drug availability in a remote area. Both types and the amount of drugs must be considered along with the drugs availability because the drugs presence is irreplaceable in health service. Therefore, drug management must be effective, efficient and in line with the needs of health services. The aim of this research is to know the profile of DRP and drug availability in remote areas. This research was conducted as descriptive research. Primary data were obtained through direct observation and conducting interview, secondary data from reviewing documents in the previous years, such as drug mutation report in IFK Belu, drug acceptance sheets as well as damaged and expired drug elimination report from 2015 until 2017. So far, DRP conducted in Belu District has been ineffective and inefficient, as observed from its drug availability which is at the very low level of ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œsecureÃƒÂ¢Ã¢â€šÂ¬Ã‚Â category. This is due to the method used in drug requirement quantification, which has not been in accordance with the standard guidelines of DRP guidelines. One of factors affecting drug availability is the amount of drug accepted as the result of the procurement, which is not in accordance with the number discrepancy of demand and drug acceptance. There were even drugs that were not delivered at all. However, the fulfillment of DRP in accordance with the National Formulary has improved in 2015 (75,6%), in 2016 (90,7%), and in 2017 (90%). Method used in counting DRP has been ineffective and inefficient, due to nonconsistent and non-thorough implementation of the plan. One of factors causing the DRP ineffectivity is insufficient drug delivery which has not reached 100% of the amount written in the procurement. However, there is annual improvement in the implementation of National Formulary as the basic of drug selection.